Pyrazolo[3, 4‐d]pyrimidine derivatives as irreversible Bruton's tyrosine kinase inhibitors. (2nd February 2022) - Yeom, Hyesu; Achary, Raghavendra; Choi, Yunha; Park, Chi Hoon; Lee, Joo‐Youn; Lee, Heung Kyoung; Kim, Pilho; Cho, Sung Yun
Abstract: 4, 6‐Disubstituted pyrazolo[3, 4‐ d ]pyrimidine derivatives were explored as irreversible Bruton's tyrosine kinase (BTK) inhibitors. The structure–activity relationship was established with over 20 derivatives synthesized to determine initial hit compounds, based on activities against BTK enzyme and TMD8 cells. It turned out that introducing 1‐acrylamido‐4‐aminopiperdine (1b ) at the C4 position of pyrazolopyrimidine as in 5e, and 3‐acrylamido‐aniline (1j ) as 4‐position substituent, such as in 9d, 10d, and 10e, delivered potent in vitro enzyme activities as well as TMD8 cell‐based cytotoxicities. Considering kinase selectivity profiles, 5e was selected for in vivo efficacy studies with a murine xenograft model using TMD8 cells, where 5e exhibited moderate tumor growth inhibition activities. Further optimization of 5e and 9d may lead to clinically useful compounds to overcome B‐cell‐mediated hematologic cancers. Abstract : The structure–activity relationship was established with over 20 derivatives of 4, 6‐disubstituted pyrazolo[3, 4‐ d ]pyrimidine against BTK enzyme and TMD8 cells. It turned out that introduction of 3‐acrylamido‐aniline at the 4‐position of pyrazolopyrimidine (9d ) delivered potent in vitro enzyme activities as well as TMD8 cell‐based activities.